2021
DOI: 10.1186/s13690-021-00683-4
|View full text |Cite
|
Sign up to set email alerts
|

Long-acting reversible contraception utilization and associated factors among women in extended postpartum period in southern Ethiopia

Abstract: Background Postpartum long-acting reversible contraceptive is important to prevent unintended and closed spaced pregnancy following the first 12 months of childbirth. Few data were available on postpartum long-acting reversible contraceptive use in Ethiopia. So, this study aimed to assess the long-acting reversible contraception use and associated factors among women who gave birth in the last 12 months. Methods A community-based cross-sectional st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
2

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 23 publications
0
2
0
Order By: Relevance
“…14 Moreover, FP slows population growth, which aids the women to possess good income potential and dedicate enough for each child, resulting in reductions in poverty. 17 The published reviews explored the variation effectiveness of contraceptive health interventions for different contraceptive outcomes. 5,18,19 The review indicated that interactive health education messages and communication with a counselor improved contraception outcomes, and the combination of unidirectional and interactive educational messages improved adherence to using contraceptives.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…14 Moreover, FP slows population growth, which aids the women to possess good income potential and dedicate enough for each child, resulting in reductions in poverty. 17 The published reviews explored the variation effectiveness of contraceptive health interventions for different contraceptive outcomes. 5,18,19 The review indicated that interactive health education messages and communication with a counselor improved contraception outcomes, and the combination of unidirectional and interactive educational messages improved adherence to using contraceptives.…”
Section: Introductionmentioning
confidence: 99%
“…14 Moreover, FP slows population growth, which aids the women to possess good income potential and dedicate enough for each child, resulting in reductions in poverty. 17…”
Section: Introductionmentioning
confidence: 99%